The Effect of Reward and Punishment on The Performance of Administrative Employees at Dr. M.M Dunda Limboto Hospital - Yolanda Ngabito; Parhamida Suma; Serly Daud (Westscience Press, 2023)
The purpose of this research is to investigate the impact that providing administrative workers with both rewards and punishments has on their performance, both individually and concurrently. The individuals who participated in this study were those who worked in the General Administration and Administration rooms, as well as those who worked in Administration at each polyclinic located inside Dr. M.M. Dunda Limboto Hospital. This research makes use of a quantitative methodology in its methodology. Techniques for collecting data through the use of questionnaires. Then, the method of sampling that is utilized is a combination of basic random sampling techniques and probability sampling. The descriptive data that was obtained is then subjected to multiple linear regression analysis with SPSS version 29. This is done after the data that was acquired has been collected. The findings of this study indicate that Reward has a positive and significant impact on the performance of administrative employees. This is evident from the fact that the t count (3.258) is higher than the t table (2.037) with a significant level of 0.03 (less than 0.05). Punishment also has a positive and significant impact on the performance of administrative employees, as evidenced by the value of the t count (3.530) with a significant level of 0.01 (less than 0.05). Furthermore, there is a simultaneous influence between Reward and Punishment on the performance of administrative employees. This is demonstrated by the fact that the F count (15.258) is higher than the F table (3.28) with a significant level of 0.01 (less than 0.05) and the R Square value obtained by 0.488. According to the chart, the effect of performance on reward and punishment accounts for 48.8 percent of the total, while the other elements are influenced by factors that are not described in this study.